Early Literacy Development of 4–5 Year Old Children through the Storytelling Method at SPS Negeri Bale Bermain Gading Kuncup Harmoni, North Jakarta - Herlina, Yuli; Yenita, Roza; Nuligar Hatiningsih; Lily Yuntina; Nina Yuminar Priyanti (CV. Creative Tugu Pena, 2025)
Literacy is a fundamental foundation for lifelong learning, yet Indonesia continues to face challenges in achieving optimal literacy outcomes, as indicated by the 2022 PISA report. Strengthening literacy from an early age is therefore crucial, and storytelling has been recognized as an effective pedagogical method to stimulate imagination, enhance oral language, and introduce children to narrative structures. This study aims to investigate the role of storytelling in fostering early literacy development among children aged 4–5 years at SPS Negeri Bale Bermain Gading Kuncup Harmoni, North Jakarta. A qualitative descriptive design was employed to capture the experiences of teachers, children, and parents. Data were collected through classroom observations, structured interviews, and document analysis, and analyzed using Miles and Huberman’s interactive model of data reduction, display, and verification, with triangulation applied to ensure validity. The findings reveal four key aspects. First, storytelling was systematically implemented in three stages: preparation, delivery, and post-story activities, supported by varied media such as puppets and picture books. Second, children responded positively by showing attentiveness, enjoyment, and active participation, with evidence of emotional and imaginative engagement. Third, early literacy development was evident in children’s ability to retell narratives, expand vocabulary, and comprehend story structures, with symbolic representation encouraged through post-story tasks. Fourth, the learning environment—characterized by quietness, comfort, inclusivity, and literacy-rich resources—was found to be essential in supporting storytelling success. This study concludes that storytelling is not merely an entertaining classroom activity but a powerful literacy strategy that enhances multiple dimensions of early literacy. The research highlights the importance of teacher creativity, environmental support, and family involvement in maximizing the potential of storytelling as an effective pedagogical tool in early childhood education.